19F DOSY NMR analysis for spin systems with nJFF couplings. (27th January 2014) - Dal Poggetto, Guilherme; Favaro, Denize C.; Nilsson, Mathias; Morris, Gareth A.; Tormena, Cláudio F.
<x xml:space="preserve">Abstract</x> NMR is a powerful method for identification and quantification of drug components and contaminations. These problems present themselves as mixtures, and here, one of the most powerful tools is DOSY. DOSY works best when there is no spectral overlap between components, so drugs containing fluorine substituents are well‐suited for DOSY analysis as 19F spectra are typically very sparse. Here, we demonstrate the use of a modified 19F DOSY experiment (on the basis of the Oneshot sequences) for various fluorinated benzenes. For compounds with significant nJFF coupling constants, as is common, the undesirable J‐modulation can be efficiently suppressed using the Oneshot45 pulse sequence. This investigation highlights 19F DOSY as a valuable and robust method for analysis of molecular systems containing fluorine atoms even where there are large fluorine–fluorine couplings. Copyright © 2014 John Wiley & Sons, Ltd.